The Effect of Growth Mindset-Based Block Play on Kindergarten Children's Social Behavior - Ni Nyoman Febiyanti; Durrotunnisa; Fitriana; Andi Agusniatih; Rafika J. Yailami; Nurul Fadila K. Daim; Cika Lianti Sotomani (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2026)
This research is motivated by the phenomenon of low social skills in group A children, which includes aspects of cooperation, interaction between individuals, and independence during learning activities. The main objective of this study is to evaluate the impact of the use of block media with the integration of growth mindset in improving social skills. Using the quantitative method of experimental design, this research involved group A participants as intervention subjects. Data were collected through structured observation techniques using social behavior assessment instruments, where the results were analyzed by comparing conditions before and after the action was given. The findings show a significant positive transformation in all indicators. The most notable increase was seen in the aspect of independence which reached the category of developing very well at 60%, followed by aspects of social interaction (53.3%) and cooperation (33.3%). Overall, these results confirm that the growth mindset-based block game strategy is very effective in optimizing early childhood social development, as well as being a reference for the application of more varied learning methods. This study contributes to the development of innovative play-based learning methods to support early childhood social development.